Korosi Baja Tulangan Pada Beton OPC, PCC, Dan OPC POFA Di Lingkungan Air Garam - Debby Mayangsari; Monita Olivia; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This paper presents the results of an experimental investigation on the steel reinforcement corrosion and sorptivity. Concretes having three type of cements (OPC, PCC, and a mixtured of palm oil fuel ash). The effect of using blended cements on the resistance of concrete against damage caused bycorrosion of the embedded reinforcement has been investigated using an halfcell potential (ASTM C876). PCC concrete showed high resistance against damage by corrosion of the steel reinforcement.Keywords : palm oil fuel ash (POFA), half-cell potential, sorptivity, concrete